READ, WRITE AND COUNT: BETWEEN CIRCULATION AND APPROPRIATION OF TEACHING METHODS IN PRIMARY SCHOOLS IN THE MEDIUM MIDLANDS OF SERGIPE (1930-1961) - Barreto, R. A. D. N. [UNESP]; Mesquita, I. M. [UNESP]; Silva, R. R. N. [UNESP] (Centro Federal Educacao Tecnologica Rio Grande Norte, 2017)
This article seeks to understand the circulation, appropriations and adaptations of teaching methods for reading, writing and arithmetic in primary school in the medium midlands of Sergipe, between 1930 to 1961. To conduct such research, we study the official documents referring to the methodology of oral history. We realize that although the State of Sergipe is circulating a modernizing discursive plan, appropriations and adaptations of teaching methods is given according to the material and intellectual conditions of time and place.
Keywords: Circulation; Appropriation; Teaching methods; Medium Midlands of Sergipe